Teaching-learning strategies through videoconferencing - Huergo Tobar, Pedro Luis (Rastros Rostros, 2015)
Introduction: this research article examines the perception of students and faculty at the School of Accounting, Economics and Management Sciences (fccea), Universidad Cooperativa de Colombia (ucc) in Neiva, based on teaching-learning strategies applied to pedagogical support.Methodology: this research has a qualitative approach with quantitative support.Results: the teaching-learning strategies used by teachers are identified and, based on results, videoconferencing mediated strategies are proposed.Conclusions: although importance is given to tutorials, students do not attend them and prefer that they are carried out by videoconference.
Keywords: teaching support; teaching-learning strategies; evad; micea; tutorials; videoconferencin